Coloniality and Racism in the Spanish Deportation System: Exceptional Practices and Violence During Deportation to Morocco - Lo Coco, Daniela (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2023)
Proponents of biopolitical approaches to migration have recently been accused of epistemological racism by those who advocate postcolonial perspectives. This article aims to contribute to the postcolonial understanding of the Spanish deportation system by focusing on its connections with racism, exception, and violence. It does so by relying on Fanon’s anti-colonial ideas, together with Mbembe’s biopolitical developments and the concept of coloniality. It analyses the deportation system as implemented in Spain and shows that it is within a legal materiality that results in racialised violence, exception and the production of death. The case of Morocco and six direct testimonies of deported nationals are studied. The analysis leads to the conclusion that the deportation system as implemented in Spain is intertwined with coloniality, exception and violence, and often produces the death of racialised groups.
Keywords: racism; postcoloniality; deportation; borders; biopolitics